If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 115 = 13x + 73 Reorder the terms: 115 + 20x = 13x + 73 Reorder the terms: 115 + 20x = 73 + 13x Solving 115 + 20x = 73 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 115 + 20x + -13x = 73 + 13x + -13x Combine like terms: 20x + -13x = 7x 115 + 7x = 73 + 13x + -13x Combine like terms: 13x + -13x = 0 115 + 7x = 73 + 0 115 + 7x = 73 Add '-115' to each side of the equation. 115 + -115 + 7x = 73 + -115 Combine like terms: 115 + -115 = 0 0 + 7x = 73 + -115 7x = 73 + -115 Combine like terms: 73 + -115 = -42 7x = -42 Divide each side by '7'. x = -6 Simplifying x = -6
| 7g+14-5gu=-8 | | 6(x-3)=2(x-11) | | 32x+48= | | 15x^3+12x=-29x^2 | | k+-17=-1 | | -6y+9(-6y-3)=2+8(1-y) | | 6m-2=2m+8 | | 2x^2+12x=7x+3 | | 2(x+9)=3(x-2) | | 4x-2+2x+8=0 | | 9x+83=5x+51 | | -5(x+1)-8x= | | -4x^2+17x-15=0 | | 15x+110=10x+70 | | 100+10x=x+15 | | 1/2+z=-6 | | 10(5x-9)=-10(10x+9) | | (4)y=12 | | 4x+2(-3x-1)-12=0 | | 9x^2+x-1=x^2-x+7 | | 0.42x=12 | | 2(x+9)=3x-2 | | 2x-(x+7)= | | q+-73=27 | | 11-7x=-10 | | -20x+119=-13x+63 | | 14x-45=5-65x | | 6x-31=4x+19 | | 3x-5=-8(6x+5) | | 6ln(2x+8)=22 | | 2-x-2(1-x)= | | -4u^2+20u-1=0 |